House ownership financing: sharia economic perspective - Safaruddin Harefa (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2021)
In determining a place to live, consumers do not only look at the price factor, but also look at the origin of the location, building, and environmental factors. The reason consumers consider the price factor is related to their incomeSo looking at the explanation from the arguments that have been described above, then the original position of the mortgage is drawn from the perspective of Islamic economics, meaning that it is the same thing using buying and selling usually, what will distinguish it is a contract that will be carried out when carrying out the mortgage process both along with third parties or related parties in this regard. Even so, this must also pay attention to the signs when buying and selling mortgages because otherwise it will form a sale and purchase contract which falls to Haram acts.